Solus Verus Deus: Francis Cheynell and the Johannine Trinity - Slavinski, Sergiej S. (Reformation & Renaissance review, 2021)
Scholars have identified the crucial importance of Johannine theology in the early modern anti-Trinitarian and Trinitarian debates. This article investigates Francis Cheynell’s defence of a Trinitarian reading of John 17:3, a highly controversial text in these debates. Modern scholarship has left implicit the significance of John 17:3. Consequently, this article argues that, from Cheynell’s perspective, John 17:3 was the key text upon which Socinian rationalism found its compelling exegetical foothold and necessitated a Trinitarian response. This article demonstrates that Cheynell, in his exegesis of John 17:3, pursued a Nicene-Augustinian metaphysical line of literal exegesis to counter the unipersonal humanist thrust of Socinian exegesis. Indeed, this article advances the thesis that Johannine theology was at the forefront of the early modern polemics surrounding the Trinity. It also highlights the importance of the influence of Nicene-Augustinian thought upon the early modern Trinitarian reception of John’s Gospel.